Semiquantitative assessment of 99mTc-MIBI uptake in parathyroids of secondary hyperparathyroidism patients with chronic renal failure - Yu, Dafu; Zou, Lin; Jin, Yao; Wei, Mingxiang; Wu, Xiaoqun; Zuo, Lingjing; Wu, Mingkang; Jiang, Yong (Frontiers in Endocrinology, 2022)
Objective: To explore the valuably influential factors and improve the diagnostic accuracy and efficiency of 99mTc-methoxyisobutylisonitrile (MIBI) uptake in parathyroids of secondary hyperparathyroidism (SHPT) patients with chronic renal failure (CRF). Methods: The correlation analysis was performed between clinical indices related to CRF and 99mTc-MIBI uptake intensity TBR (the gray value mean ratio between parathyroid target and bilateral neck background, semiquantitatively calculated with software ImageJ). All above clinical indices and TBRs were compared by 3-level or 2-level grouping method of MIBI uptake which was visually qualitatively assessed. 3-level grouping method comprised slight, medium and high groups with little, faint and distinct MIBI concentration in parathyroids, respectively. 2-level grouping method comprised insignificant and significant groups with TBR greater or less than 0.49 – 0.71, respectively. Results: MIBI uptake was significantly positively related to patient age, CRF course, hemodialysis vintage, serum parathyroid hormone (PTH) and alkaline phosphatase (AKP), but was significantly negatively related to serum uric acid (UA). MIBI washout was significantly positively related to patient age, but was significantly negatively related to serum phosphorus (P) and calcium (Ca)  P. Oral administration of calcitriol and calcium could significantly reduce MIBI uptake. MIBI uptake tendency might alter. Such 7 indices as the MIBI uptake, CRF course, hemodialysis vintage, serum AKP, calcium, cysteine proteinase inhibitor C and PTH were comparable between slight and medium group, but were significantly different between slight and high group, or between medium and high group. The above 7 indices plus blood urea nitrogen/Creatinine were all significantly different between insignificant and significant group. All above significances were with P < 0.05. Conclusions: Patient age, CRF course, hemodialysis vintage, serum PTH, AKP, UA, phosphorus, Ca  P, oral administration of calcitriol and calcium, and parathyroids themselves could significantly influence MIBI uptake in parathyroids of SHPT patients with CRF. 2-level grouping method of MIBI intensity should be adopted to qualitatively diagnose MIBI uptake.